Conversion between location identification and GPS coordinate - Chang, En You. (2010)
GPS (Global Positioning System) technology has been widely integrated in many personal navigational products for our everyday living. Today, GPS systems are also frequently found in various non-navigational applications, such as digital cameras, in which precise positioning is needed to record the venue where the photo are taken. This report contains information on the ideas, process and problems encountered during the duration of the project entitled “Conversion between Location Identification and GPS Coordinate”. The project is to develop a database together with a set of software programs for storing and retrieving GPS coordinates and to convert the coordinates into known locations indentified with names. The project is divided into three phases. Firstly, online database using MS access was developed for storing of locations and GPS coordinates. The database system includes the function of viewing, adding, deleting and updating of records. In the second phase, software programs for error checking of user’s input and browser’s interface were implemented. The purpose of the error checking mechanism is to prevent user from inputting invalid queries. In the last stage, GPS data is retrieved from the EXIF header of geo-tagged photos to identify the location where the photos are taken. The application is developed based on server scripting language ASP and client scripting language Javascript using IIS as the server environment. The report describes the database created, the methods for storing and retrieving the GPS information, the GUI developed and the implemented software programs.